2010
DOI: 10.1074/jbc.m109.035741
|View full text |Cite
|
Sign up to set email alerts
|

Yellow-e Determines the Color Pattern of Larval Head and Tail Spots of the Silkworm Bombyx mori

Abstract: Yellow proteins form a large family in insects. In Drosophila melanogaster, there are 14 yellow genes in the genome. Previous studies have shown that the yellow gene is necessary for normal pigmentation; however, the roles of other yellow genes in body coloration are not known. Here, we provide the first evidence that yellow-e is required for normal body color pattern in insect larvae. In two mutant strains, bts and its allele bts2, of the silkworm Bombyx mori, the larval head cuticle and anal plates are reddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 26 publications
(34 reference statements)
2
35
0
1
Order By: Relevance
“…In P. xuthus and B. mori larvae, the expression of yellow-y genes, PxY-y and BmY-y, is also consistent with the appearance and patterning of black pigmentation. Very recently, Ito et al (2009) reported that BmY-e is also required for the normal larval body color pattern in B. mori. However, the exact physiological functions of most yellow genes are still little understood.…”
Section: Genementioning
confidence: 99%
“…In P. xuthus and B. mori larvae, the expression of yellow-y genes, PxY-y and BmY-y, is also consistent with the appearance and patterning of black pigmentation. Very recently, Ito et al (2009) reported that BmY-e is also required for the normal larval body color pattern in B. mori. However, the exact physiological functions of most yellow genes are still little understood.…”
Section: Genementioning
confidence: 99%
“…Positional cloning revealed that yellow-e accounts for the phenotype of bts (brown tail spot, larval head cuticle and anal plates are reddish brown color instead of white) (Ito et al, 2010). A 126 bp deletion in the genome caused the loss of arylalkylamine N-acetyltransferase activity which is responsible for mln (melanism, black moth) Zhan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many body color mutants have been obtained in Bombyx mori, including lemon (lemon lethal) (Meng et al, 2009), ch, so , bts (Ito et al, 2010), mln Zhan et al, 2010), and sch , and have been characterized molecularly. It was found that mutations in the sepiapterin reductase (SPR) gene (Bmspr) are responsible for the yellow body coloration of the lemon and lemon lethal mutations (Meng et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the independent and stable phenotypic defects are likely to be due to functional redundancy among the gene family members in insects. Recent research has shown that the yellow-e protein determines the silkworm bts mutant (Ito et al, 2010), which exhibits a similar…”
Section: Discussionmentioning
confidence: 99%
“…Within lepidopteran species, the silkworm is considered a suitable model for the genetic and molecular identification of traits owing to its substantial economic value (Fujii et al, 1998;Goldsmith et al, 2005), abundantly maintained variants and widely available genetic and genomic resources (Mita et al, 2004;Xia et al, 2004;Miao et al, 2005;International Silkworm Genome Consortium, 2008;Yamamoto et al, 2008;Zhan et al, 2009). Recently, several larval mutants have been identified for this well-studied model (Futahashi et al, 2008;Ito et al, 2009;Meng et al, 2009b;Ito et al, 2010), including novel models outside of the classical insect melanin synthesis pathway (Ito et al, 2009;Meng et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%